Smart Saklar Prototipe Menggunakan Android - Noor Yulita Dwi Setyaningsih (E-JOINT (Electronica and Electrical Journal Of Innovation Technology), 2022)
In our daily activities, we can never be far from using electronic devices either at home or at work. And we always use a switch to control the on or off of the electronics that we will use, for example, the use of lights, room curtains, or fans. So far, we still use manual switches that are mounted on the wall to turn on or turn off the electronics. In this research opportunity, a smart switch will be used that utilizes an android application that can be accessed by a cellphone to carry out controls to turn on or turn off electronic devices. There are many advantages, where electronic users can access where they are and this research utilizes Bluetooth communication for communication between android and existing hardware systems. The results of the study obtained a system success rate of 100% with a maximum control distance that can be used as far as 15 meters without interference and 10 meters with interference.